A Comparative Study Of The Adaptation Process And Stress Among Regular And Transfer Students During The Thesis Writing Process At STIKes Karsa Husada Garut - Muchammad Sidiq Nurzaman; Andhika Lungguh Perceka (Science and Education Journal (SICEDU), 2026)
Thesis is the final task that must be done by the student as one of the requirements in obtaining his bachelor degree. In the process of formulation of students meet various kinds of difficulties so that it becomes a pressure on students who will cause stress. Stress is a condition of physical and psychological pressure due to the demands of the self and the environment. Students who are preparing a thesis should be able to adapt in the face of stress and obstacles they experienced. Stress should be anticipated and managed appropriately so that the process of adaptation in the preparation of the thesis does not cause a maladtive range. This study uses a comparative descriptive method. The sample is determined by simple random sampling approach, with 84 people consisting of 38 regular students and 46 transfer students, while for the data collecting of the researcher using questioner. After testing the hypothesis at the stress level obtained results p value: 0,554> alpha (α = 0,05). This indicates that Ha is rejected, ie there is no difference in stress level between regular students and transfer students. With the average result of normal stress level. While in hypothesis testing of adaptation process got p value: 0,024 <alpha (α = 0,05), this mean Ha accepted that show difference of process of adaptation between student of regular and transfer student. With the difference of transfer students more maladaptif than regular students are more adaptive, this happens because transfer students experience some obstacles in the process of arranging the scheme of them is because the focus of attention transfer students diverted by work and family. It is expected that the education can improve the support, facilities and policies to support the smoothness of students in the process of preparing the thesis. For students who will prepare the thesis is expected to add insight about stress and adaptation so that it can be a motivation in completing the process of preparing the thesis.